Pelatihan Peningkatan Kualitas Sumber Daya Manusia di Era Digital pada UMKM - Mansyur, Abdul; Mustafa, Yushar; Data, Muhammad Umar; Sulfati, Andi; Djamali, Hisnol (Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
This community service activity is carried out with the aim of increasing knowledge and skills in human resource management (HR) in MSME (Micro, Small and Medium Enterprises) companies. HR Management Training in the Digital Era is a training program designed to equip HR professionals with relevant and up-to-date skills in managing human resources in the digital era. This kind of training is designed to prepare HR professionals to face the challenges arising from the ongoing digital transformation. The method of implementing this activity is carried out using a material presentation model and followed by discussion activities. This training activity was attended by 16 MSME scale business actors from Badung district, Bali. From the results of the training, it was concluded that several weaknesses were found in MSME businesses, especially in DM management, such as lack of digital skills, uncertainty about change, lack of access to digital resources, inability to compete with large companies and data security and privacy.